Structural, optical and electrical properties of nanocomposites of PVA/PANI/nickel nanoparticles synthesized by gamma radiolytic method - Meftah, Abdo Mohammed Ali; Gharibshahi, Elham; Soltani, Nayereh; Mat Yunus, Wan Mahmood; Saion, Elias (MDPI, 2014)
This article reports a simultaneous synthesis of polyaniline (PANI) and nickel (Ni) nanoparticles embedded in polyvinyl alcohol (PVA) film matrix by gamma radiolytic method. The mechanism of formation of PANI and Ni nanoparticles were proposed via oxidation of aniline and reduction of Ni ions, respectively. The effects of dose and Ni ions concentration on structural, optical, and electrical properties of the final PVA/PANI/Ni nanocomposites film were carefully examined. The structural and morphological studies show the presence of PANI with irregular granular microstructure and Ni nanoparticles with spherical shape and diameter less than 60 nm. The average particle size of Ni nanoparticles decreased with increasing dose and decreasing of precursor concentration due to increase of nucleation process over aggregation process during gamma irradiation. The optical absorption spectra showed that the absorption peak of Ni nanoparticles at about 390 nm shifted to lower wavelength and the absorbance increased with increasing dose. The formation of PANI was also revealed at 730 nm absorption peak with the absorbance increasing by the increase of dose. The electrical conductivity increased with increasing of dose and chlorine concentration due to number of polarons formation increases in the PVA/PANI/Ni nanocomposites.